Frankenstein or a Submarine Alkaline Vent: Who Is Responsible for Abiogenesis?: Part 1: What is life–that it might create itself?. (5th June 2018) - Branscomb, Elbert; Russell, Michael J.
Abstract : Origin of life models based on "energized assemblages of building blocks" are untenable in principle. This is fundamentally a consequence of the fact that any living system is in a physical state that is extremely far from equilibrium, a condition it must itself build and sustain. This in turn requires that it carries out all of its molecular transformations–obligatorily those that convert, and thereby create, disequilibria–using case‐specific mechanochemical macromolecular machines. Mass‐action solution chemistry is quite unable to do this. We argue in Part 2 of this series that this inherent dependence of life on disequilibria‐converting macromolecular machines is also an obligatory requirement for life at its emergence. Therefore, life must have been launched by the operation of abiotic macromolecular machines driven by abiotic, but specifically "life‐like", disequilibria, coopted from mineral precipitates that are chemically and physically active. Models grounded in "chemistry‐in‐a‐bag" ideas, however energized, should not be considered. Abstract : The authors argue that the thermodynamics of far‐from‐equilibrium systems dictates that life cannot have emerged from molecular mixtures of any character no matter how they might be activated by energy inputs. And further that the only model for abiogenesis consistent with these thermodynamic principles is the alkaline hydrothermal vent theory.